A logarithmically improved regularity criterion for the 3D Hall-MHD equations in Besov spaces with negative indices. Issue 16 (10th December 2017) - Ye, Zhuan
Abstract : In this paper we consider the three dimensional (3D) incompressible Hall-magnetohydrodynamic equations (Hall-MHD). It is proved that the local smooth solution can be continued beyond time T provided that the velocity u and the magnetic field B satisfy for . As a consequence, this result extend the previous result.